Financial strategy to accelerate green growth - Hee Jin Noh (Asian Development Bank Institute (ADBI), 2018)
Green growth simultaneously seeks economic development and environmental enhancement. In order to support green growth financially, the green finance sector needs to be developed. Funding and investment mechanisms of green finance are different from that of non-green finance, because green finance needs to consider green value in its financial activities. The role of public finance is important, but limited in its support of green growth because a huge amount of money is needed. Because of this large requirement, the role of private finance is essential. However, under the current private financial mechanism, green fields are difficult to invest in because the risk and return profile of the fields are different from those of traditional industries. Therefore, green finance is needed. Throughout this chapter, strategies for developing green finance are suggested. They include improving rules and regulations of green finance to seek green growth, establishing green financial institutions, utilizing the Green Climate Fund designing a code of conduct for green finance, developing new green financial products, integrating a global cooperative system, and setting up infrastructure.
Keywords: G2; 330; green growth; green finance; Green CAPM; public-private partnership; emission trading system